Clinical adaptation of auxiliary methods and multidisciplinary approach to changing trends in parathyroid surgery. Issue 39 (1st October 2021) - Aydin, Husnu; Dural, A. Cem; Sahbaz, N. Alper; Karli, Merve; Guzey, Deniz; Akarsu, Cevher; Ferahman, Sina; Piskinpasa, Hamide; Yegul, Duygu; Sipahi, Murat; Koyuncu, Aysel; Altinay, Serdar; et al.
Abstract : Abstract: To examine the effects of multidisciplinary approach and adjunct methods, on the surgical strategy, complications and treatment success of parathyroid surgery. Patients, who were operated for primary hyperparathyroidism (n = 411) at our institution between 2012 and 2019 were reviewed retrospectively. Preoperative imaging studies, surgical method, additional diagnostic methods used during surgery, frozen section results, and histopathology findings, complications, persistence, and recurrence were examined. Localization was determined by first-line examinations in 79.9% (n = 348). Four-dimensional computed tomography was used with an 83.3% success rate. Lateralization success for angiographic selective venous sampling was 80.3% and exact localization success was 65.1%. Bilateral neck exploration was performed in 10.6% (n = 37) of the patients, and in the remaining 89.4% (n = 311), minimally invasive parathyroidectomy (MIP) was performed. While the complication rate was higher in the bilateral neck exploration group ( P = .019), persistence and recurrence rates were similar between 2 groups. During the study period, annual case volume increased from 9 cases to 103 cases ( P < .001) and the rate of MIP increased from 44.4% to 92.8% over the years ( P < .001). Effective use of adjunct techniques has increased the rates of MIP. The multidisciplinary approach has also provided low complication rates with the increasing number of cases.